Mouse BAC Ends Quality Assessment and Sequence Analyses - Zhao, Shaying; Shatsman, Sofiya; Ayodeji, Bola; Geer, Keita; Tsegaye, Getahun; Krol, Margaret; Gebregeorgis, Elizabeth; Shvartsbeyn, Alla; Russell, Daniel; Overton, Larry; Jiang, Lingxia; Dimitrov, George; et al.

(untitled) (Genome Research, 2001)
A large-scale BAC end-sequencing project at The Institute for Genomic Research (TIGR) has generated one of the most extensive sets of sequence markers for the mouse genome to date. With a sequencing success rate of >80%, an average read length of 485 bp, and ABI3700 capillary sequencers, we have generated 449,234 nonredundant mouse BAC end sequences (mBESs) with 218 Mb total from 257,318 clones from libraries RPCI-23 and RPCI-24, representing 15× clone coverage, 7% sequence coverage, and a marker every 7 kb across the genome. A total of 191,916 BACs have sequences from both ends providing 12× genome coverage. The average Q20 length is 406 bp and 84% of the bases havephred quality scores ≥ 20. RPCI-24 mBESs have more Q20 bases and longer reads on average than RPCI-23 sequences. ABI3700 sequencers and the sample tracking system ensure that > 95% of mBESs are associated with the right clone identifiers. We have found that a significant fraction of mBESs contains L1 repeats and ∼48% of the clones have both ends with ≥ 100 bp contiguous unique Q20 bases. About 3% mBESs match ESTs and > 70% of matches were conserved between the mouse and the human or the rat. Approximately 0.1% mBESs contain STSs. About 0.2% mBESs match human finished sequences and > 70% of these sequences have EST hits. The analyses indicate that our high-quality mouse BAC end sequences will be a valuable resource to the community.